Nanostructural glasscomposite self-lubricant coatings - Fialko, N.M.; Shchepetov, V.V.; Kharchenko, S.D.; Kovtun, S.I.; Hladkyi, Ya. N.; Bys, S.S. (Problems of Tribology, 2022)
The results of the study of glass-composite nanostructured self-lubricating coatings are presented. The structural components of these coatings significantly affect the graphitization process and provide an antifriction surface layer of α-graphite. The formation of this layer makes it possible to significantly minimize the contact parameters in the friction region. A significant effect of aluminoborosilicate in the form of a glass phase on the tribological properties of coatings is noted. An increase in adhesive strength is achieved by forming a surface layer of glassy sodium silicate. The presence of near-surface particles in the graphite layer does not affect the tribotechnical characteristics of the coatings. The developed glass-composite nanostructured self-lubricating coatings have high antifriction characteristics throughout the entire load-speed range